2020
DOI: 10.3390/ma13153244
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Alloy Surfaces and Cleaning Regimens against the Spread of SARS-CoV-2 in Dentistry and Orthopedics. From Fomites to Anti-Infective Nanocoatings

Abstract: The latest diffusion of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for the coronavirus disease (COVID-19), has involved the whole world population. Even if huge efforts to control the pandemic have been done, the viral spread is still continuing. COVID-19 is reported as a zoonosis jumped from bats and pangolins to humans. After infection in humans, SARS-CoV-2 is found in the nasopharyngeal and salivary secretions. The virus has also been detected in the blood plasma of infected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 64 publications
(84 reference statements)
0
51
0
Order By: Relevance
“…It has been established and confirmed that the transmission routes are via contact (human and surface contacts), droplet and airborne spread and many of these were described in the articles reviewed and are recorded on the Tables [1,[6][7][8][9][10][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. It is well known that many dental procedures regularly produce aerosols and droplets which normally may be contaminated with bacteria, viruses and blood and may easily spread to the dental personnel and other patients within these settings [7][8][9][10]. In addition, the contact between different surfaces that naturally occur in the dental setting may further contribute to the spread of any harmful substances, including COVID-19 from unsuspected or asymptomatic patients or dental personnel.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…It has been established and confirmed that the transmission routes are via contact (human and surface contacts), droplet and airborne spread and many of these were described in the articles reviewed and are recorded on the Tables [1,[6][7][8][9][10][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. It is well known that many dental procedures regularly produce aerosols and droplets which normally may be contaminated with bacteria, viruses and blood and may easily spread to the dental personnel and other patients within these settings [7][8][9][10]. In addition, the contact between different surfaces that naturally occur in the dental setting may further contribute to the spread of any harmful substances, including COVID-19 from unsuspected or asymptomatic patients or dental personnel.…”
Section: Discussionmentioning
confidence: 75%
“…Well-meaning dentists who want to serve the needs of their patients as they should may be spreading the virus faster and extensively, without being aware of it [2, 5,7]. Therefore guidelines and standard operating procedures, which encompass their clinical work, work space as well as the principles guiding their practices, must be well formulated and strictly followed to protect themselves, dental staff and the patients they serve [2][3][4][5][6][7][8][9]. But what is it about the nature of their clinical work that places them and their patients at greater risk of developing COVID-19 or any similarly infectious viral diseases?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao et al went on to analytically investigate how fomite transmission of SARS infections were found to play a non-negligible role in pathogen transmission throughout a simulated hospital setting. The study by Xiao et al is only one of a number of similar works attesting to the fact that preventative measures need to be taken to minimize the risk of infection associated with touching an infected surface when SARS-based coronavirus outbreaks occur [2][3][4][5] . Otter et al found that SARS-CoV, MERS-CoV, and the influenza virus was shed from an infected community member within a hospital-like setting at concentrations that are much greater than the dose required for infection 6 .…”
Section: Fomite Transmission Of Viral Pathogens and Sars-cov-2mentioning
confidence: 99%
“…They act as carriers for target-based delivery of antigens against viruses. Metal nanoparticles can adhere to the viral envelope, the membrane of cells, and then enter the interior, destroying genetic materials such as DNA and RNA [ 3 ] ( Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%